Mathematics base for navigation mobile robot using reachability petri net - Gunardi, Yudhi; Hanafi, Dirman; Supegina, Fina; Adriansyah, Andi (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Navigation is the journey that brings the precision and accuracy especially for the trip from one place to many destinations. Traveling mobile robot will be challenged when there are plenty of travel options and obstacles; it is necessary for special methods to deal with this. Petri net modeling is one method that can be applied in this navigation. As a model network graph, Petri net can be seen as a model of superior visuals for their token moves that define the process dynamics of a system. Other models that have been provided, such as flow charts, block diagrams or network topology, are using the method of mathematical reachability. Meanwhile Petri net obtained the navigation as a result of marking the value. The final results of this research is that Petri net can be used to obtain mobile robot for navigation.